Perancangan Aplikasi Media Informasi Lembaga Kursus Berbasis Web - Muhammad Iqbal Panjaitan; Zekson Arizona Matondang (Yayasan Kita Menulis, 2019)
Abstract-Website can be interpreted as a collection of pages that are used to publish information in the form of text, images and other multimedia programs in the form of animation (motion pictures, motion writings), sound, and or a combination of all of them both static and dynamic that form one a series of interrelated buildings between one page and another page. In this paper the design of applications that can be used as part of the dissemination of information to course institutions to increase the introduction of these agencies, to the design through the DFD design, database relation design and form design will be used as a reference in making websites.